Air Pollution: Role of Extracellular Vesicles-Derived Non-Coding RNAs in Environmental Stress Response - Giuseppa D’Amico; Radha Santonocito; Alessandra Maria Vitale; Federica Scalia; Antonella Marino Gammazza; Claudia Campanella; Fabio Bucchieri; Francesco Cappello; Celeste Caruso Bavisotto (Cells, 2023)
Air pollution has increased over the years, causing a negative impact on society due to the many health-related problems it can contribute to. Although the type and extent of air pollutants are known, the molecular mechanisms underlying the induction of negative effects on the human body remain unclear. Emerging evidence suggests the crucial involvement of different molecular mediators in inflammation and oxidative stress in air pollution-induced disorders. Among these, non-coding RNAs (ncRNAs) carried by extracellular vesicles (EVs) may play an essential role in gene regulation of the cell stress response in pollutant-induced multiorgan disorders. This review highlights EV-transported ncRNAs’ roles in physiological and pathological conditions, such as the development of cancer and respiratory, neurodegenerative, and cardiovascular diseases following exposure to various environmental stressors.